2004
DOI: 10.1080/02827580410017816
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and ecotoxicology of furfurylated wood

Abstract: Chemistry and ecotoxicology of furfurylated wood. Scand. J. For. Res. 19(Suppl. 5): 14 Á/21, 2004.Over the past decade modernized processes for furfurylation of wood have been developed. These new processes are based on completely new catalytic systems and process additives. These new systems do not add metals or halogens to the product, which is important for an environmentally acceptable product. However, little is known about the ecotoxicity of furfurylated wood or other environmental impacts that may resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 7 publications
8
57
1
Order By: Relevance
“…By using cyclic carboxylic anhydrides, mainly maleic anhydride, as key catalysts, furfurylated wood, having properties superior to those produced with the early developed systems, was achieved by Prof. M. Schneider (1995) in Canada. Novel research was also carried out by Dr. M. Westin and his coworkers (Westin 1996;Westin et al 1998;Lande et al 2004aLande et al , 2004b, at SP Sweden, which led to a new technology based on stable solutions with good impregnating capacity, as well as some promising properties such as resistance to decay.…”
Section: Furfurylationmentioning
confidence: 99%
See 2 more Smart Citations
“…By using cyclic carboxylic anhydrides, mainly maleic anhydride, as key catalysts, furfurylated wood, having properties superior to those produced with the early developed systems, was achieved by Prof. M. Schneider (1995) in Canada. Novel research was also carried out by Dr. M. Westin and his coworkers (Westin 1996;Westin et al 1998;Lande et al 2004aLande et al , 2004b, at SP Sweden, which led to a new technology based on stable solutions with good impregnating capacity, as well as some promising properties such as resistance to decay.…”
Section: Furfurylationmentioning
confidence: 99%
“…The possible cross-linking patterns of furfuryl alcohol polymer chains have been proposed by González et al (1992), who demonstrated that the high amount of permanent wood cell-wall bulking in the furfurylated wood is evidence of the grafting reactions at early polymerization stages. In addition, it has been concluded (González et al 1992;Lande et al 2004b) that with the catalytic systems used for furfurylation of wood it is more likely that grafting to hemicelluloses and most of all to lignin is dominant. As a consequence, a possible grafting reaction between the furfuryl alcohol and a guaiacyl unit of lignin (the predominant unit in softwood lignins) is evidently probable.…”
Section: Furfurylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The slight deviations could be explained by differences in the anatomical structure and the high resolution of the individual measuring fields. In general, the individual parameters of the FA modification (in terms of catalyst concentration, processing temperature and time and pH value of the solution) strongly affect the final product by the degree and type of chemical bonds (Lande et al 2004a). …”
Section: Uv Microscopic Scanning Profilesmentioning
confidence: 99%
“…Furfuryl alcohol (FA) is obtained from renewable resources of agricultural crop waste (corn or sugar cane production) consisting of pentosans, which are easily hydrolyzed, and the pentoses obtained are dehydrated to furfural (F) (Hill 2006;Uppal et al 2008;Moghaddam et al 2016), which is then converted to FA. F and FA are by far the most important furan derivates (Gandini and Lacerda 2015), which can be polymerized by several organic and mineral acids, such as by Lewis acids (Lande et al 2004a). Ünver and Öktem (2013) investigated controlled cationic polymerization of FA, visualized by the UV bands at λ 228 nm and λ 286 nm .…”
Section: Introductionmentioning
confidence: 99%